Practices of environmental education in primary school: a scoping review - Stefania Falchi; Antioco Luigi Zurru (Firenze University Press, 2024)
This work presents the results of an exploratory systematic review involving quantitative, qualitative, and mixed-methods empirical studies in A-class (ANVUR) journals. The research's objective was to identify effective educational practices and environmental education activities aimed at developing knowledge and promoting pro-environmental and eco-sustainable attitudes in primary schools (ages 6-12). Article selection was carried out through disciplinary and general databases, resulting in the identification of 14 articles meeting the selection criteria. The literature synthesis allowed for the identification, analysis, and description of some effectiveness traits useful in guiding research and educational practices toward ecological transition.   Pratiche di educazione ambientale nella scuola primaria: una scoping review. Questo lavoro presenta gli esiti di una revisione sistematica a scopo esplorativo che coinvolge studi empirici quantitativi, qualitativi e mixed-methods in riviste di classe A (ANVUR). L'obiettivo della indagine è stato quello di individuare pratiche educative efficaci e attività didattiche di educazione ambientale finalizzate allo sviluppo di conoscenze e alla promozione di atteggiamenti pro-ambientali ed eco-sostenibili nella scuola primaria (6-12 anni). Il processo di selezione degli articoli è avvenuto tramite database disciplinari e generici e ha permesso di identificare 14 articoli rispondenti ai criteri di selezione. La sintesi di letteratura ha consentito di individuare, analizzare e descrivere alcuni caratteri di efficacia, utili a indirizzare la ricerca e la pratica didattica verso la transizione ecologica.